ChemInform Abstract: Facile Synthesis of Pyrimidines via Iminium Catalyzed [4 + 2] Reaction of α, β‐Unsaturated Ketones with 1, 3, 5‐Triazines. Issue 15 (24th March 2016) - Yang, Gongming; Chen, Lei; Wang, Jian; Jia, Qianfa; Wei, Jia; Du, Zhiyun
Abstract: An iminium‐catalyzed Diels—Alder reaction of 1, 3, 5‐triazines with α, β‐unsaturated ketones is developed.